Improving the performance of RC beam with circular opening using hybrid fibres - Luqman, Umar (2018)
The research presents the study of overcoming the loss of strength inside RC beams with opening by the use of hybrid fibre. In order to overcome the loss of strength inside the RC beam with opening, mixture of kenaf fibre and steel fibre (hybrid fibre) was added during the concrete mix design. This study includes four beam sample which is three RC beams with circular opening at the centre that were added 1% hybrid fibre and 2% hybrid fibre, while the other two RC beams are mix without hybrid fibre with one of the RC beam includes circular opening to be used as reference control beam. Apart from that, the testing involved are the slump test, cube test, and flexural test. This test was conducted to obtain the exact value of the maximum load that the test sample can withstand. Comparison among the test sample are to be made with all the data collected. The expected outcome of this research is the increase in performance that includes strength and durability in beams with opening that were added hybrid fibre. The result obtained in the end of the experiment showed that Vf=1% and Vf=2% managed to increase the strength and changed the failure mode from bending to shear.